2005
DOI: 10.4049/jimmunol.174.12.7746
|View full text |Cite
|
Sign up to set email alerts
|

An MHC Class Ib-Restricted TCR That Cross-Reacts with an MHC Class Ia Molecule

Abstract: TCR transgenic 6C5 T cells recognize an insulin B chain epitope presented by the nonclassical class I MHC molecule, Qa-1b. Positive selection of these T cells was shown previously to require Qa-1b. Despite dedicated specificity for Qa-1b, evidence presented in the current study indicates that 6C5 T cells can cross-recognize a classical class I molecule. Clonal deletion was observed unexpectedly in 6C5.H-2bxq mice, which do not express I-E MHC class II molecules and thus should not be subject to superantigen-me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
1
3
0
Order By: Relevance
“…Importantly, we showed that thymus selection of our Qa-1 b T cell specificity was independent of the presence of Qa-1 b (see Figure 5 ), indicating that these TCRs engage other MHC class I molecules for positive selection in the thymus and then “cross-react” to peptide/Qa-1 b complexes in the periphery. Such cross-reactivity between classical and non-classical MHC molecules was reported before ( 42 , 43 ) and underlines the similarities of their structures ( 7 ). Together, these results implicate limited availability of suitable TCRs and, therefore, low T cell precursor frequencies, to target each peptide-epitope presented by Qa-1 b .…”
Section: Discussionsupporting
confidence: 84%
“…Importantly, we showed that thymus selection of our Qa-1 b T cell specificity was independent of the presence of Qa-1 b (see Figure 5 ), indicating that these TCRs engage other MHC class I molecules for positive selection in the thymus and then “cross-react” to peptide/Qa-1 b complexes in the periphery. Such cross-reactivity between classical and non-classical MHC molecules was reported before ( 42 , 43 ) and underlines the similarities of their structures ( 7 ). Together, these results implicate limited availability of suitable TCRs and, therefore, low T cell precursor frequencies, to target each peptide-epitope presented by Qa-1 b .…”
Section: Discussionsupporting
confidence: 84%
“…H2-M3-restricted T cells are positively selected by haematopoietic cells in the thymus, which was suggested to result from a high-affinity interaction between TCR and class Ib [51]. Evidence also suggests that Qa-1 b -restricted T cells can be positively selected through weak interactions with MHC class Ia molecules [55]. Alternatively, the selection of a class-Ib-restricted Tcell repertoire might occur in a similar way as occurs for T cells restricted by MHC class Ia molecules.…”
Section: Discussionmentioning
confidence: 95%
“…The MHC-E restricted response to a CMV-vectored HIV vaccine showed extremely broad reactivity, with detectable responses to 4 epitopes for every 100 amino acids 56 . In addition, another Qa1 b restricted clone was shown to cross react with an MHC Ia molecule 57 , although it was dependent on Qa1 b for its positive selection 9 . In this regard, it is intriguing that QFL T cells show strong preferential use of Va3.2 (encoded by TRAV9N/D-3) 36 .…”
Section: Discussionmentioning
confidence: 99%